Cuidado ao paciente idoso hospitalizado: implicações para a equipe de enfermagem - Banja, Paula Fernanda Tieko [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
The Brazilian population is ageing rapidly, and chronic diseases have increased. Due to deficient health care services, the diagnosis and treatment of such diseases occur in the tertiary level, which increases costs and reduces the possibilities of early diagnoses. In view of the elderly population‟s increase and of the great demand at hospitalization units, it is important to learn about the difficulties and facilities faced by nursing teams when giving care to hospitalized individuals. In order to reach the objectives, a cross-sectional, prospective, descriptive, analytical and qualitative study was performed with basis on Bardin‟s Content Analysis. Among the difficulties were patients‟ limitations, dependence level, behaviors and habits, interference from companions, feeling of abandonment, perception of needs, dealing with suffering and lack of time for adequate care. As to facilities, acceptance of the disease, adherence to treatment, collaboration, trust in the team, and older patients‟ politeness were reported, which shows that passiveness is an important indicator in caring for the elderly. Older individuals suffer the outcomes of certain physical, psychological and mental deficits. When facing disease conditions, they require special care, including hospitalization and greater attention. The nursing team provides daily care and follows patients‟ development; however, its members are still not knowledgeable enough about the ageing process. This contributes to increase prejudice and erroneous stereotypes about older persons. Therefore, not understanding such process compromises the full care to be provided to older patients. This leads team members to accelerate the care provision process in order to meet the daily work demand, thus compromising older patients‟ autonomy and making them more dependent on the team, whereas the process should follow the opposite path

O envelhecimento da população brasileira está ocorrendo de forma rápida culminando com o aumento das doenças crônicas. Por haver a deficiência de serviços de saúde, o diagnóstico e tratamento dessas doenças ocorrem a nível terciário, elevando os custos e reduzindo as possibilidades de diagnóstico precoce. Diante do crescente aumento da população idosa e da grande demanda nas unidades de internação, é importante conhecer as dificuldades e facilidades que a equipe de enfermagem enfrenta no cuidado ao idoso hospitalizado. Para atingir os objetivos foi realizado estudo transversal, prospectivo, descritivo e analítico, de abordagem qualitativa, baseado no método de Análise de Conteúdo de Bardin. Entre as dificuldades tiveram-se as limitações dos pacientes, grau dependência, comportamentos e hábitos, interferência de acompanhantes, sentimento de abandono, percepção das necessidades, lidar com o sofrimento e a falta de tempo para assistência adequada. Quanto às facilidades foi explicitado a aceitação da doença, adesão do tratamento, colaboração, confiança na equipe e o idoso ser educado, indicando que a passividade é um indicador importante no cuidado com o idoso. O idoso sofre conseqüências de certos déficits físicos, psicológicos e emocionais. Em situação de doença necessita de cuidados especiais incluindo a internação e maior atenção. A equipe de enfermagem é que executa cuidados diários e evolução dos pacientes, no entanto, ainda não possui conhecimento suficiente sobre o envelhecimento. Isso contribui para o aumento dos preconceitos e estereótipos equivocados sobre o idoso. Portanto a não compreensão desse processo compromete a assistência integral do paciente idoso. Isso faz com que o indivíduo que compõem a equipe acelere o processo assistencial para vencer a demanda de trabalho diário, comprometendo... (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Idosos - Cuidados medicos; Enfermagem geriatrica